Effect of polymer concentration on morphology, dielectric and optical properties in a polymer-dispersed ferroelectric liquid crystal. Issue 5 (8th April 2016) - Jayoti, Divya; Khushboo,; Malik, Praveen; Singh, Arshdeep
ABSTRACT: Photocurable polymer-dispersed ferroelectric liquid crystal were prepared by polymerisation-induced phase separation (PIPS). Morphological behaviour was analysed by polarising optical microscopy (POM) and scanning electron microscopy (SEM). FLC droplet size was found in the range of 2–70 µm and decreases with an increase in polymer content. Relaxation frequency, dielectric strength and ac conductivity were evaluated as a function of polymer concentration and it was concluded that the polymer concentration has a significant effect on these parameters. The energy band gap ( ) increases with polymer concentration and was found in the range of 3.3 eV at higher concentration of polymer. Graphical Abstract: